2013
DOI: 10.1007/s13277-013-0831-y
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between breast cancer stem cells and metastatic niche: emerging molecular metastasis pathway?

Abstract: Metastatic colonization represents the final step of metastasis, and is the major cause of cancer mortality. Metastasis as an "inefficient" process requires the right population of tumor cells in a suitable microenvironment to form secondary tumors. Cancer stem cells are the only capable population of tumor cells to progress to overt metastasis. On the other hand, the occurrence of appropriate microenvironmental conditions within the target tissue would be critical for metastasis formation. Metastatic niche se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 123 publications
1
37
0
Order By: Relevance
“…So by considering above-mentioned facts, we hypothesized that there might be a regulatory connection between these major players and factors in breast cancer metastasis [8]. Having these seminal previous works as backbone, in this study we show that expression of TNC and POSTN is correlated and consistent with that of SLUG and SOX9, when the latter are simultaneously expressed.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…So by considering above-mentioned facts, we hypothesized that there might be a regulatory connection between these major players and factors in breast cancer metastasis [8]. Having these seminal previous works as backbone, in this study we show that expression of TNC and POSTN is correlated and consistent with that of SLUG and SOX9, when the latter are simultaneously expressed.…”
Section: Introductionsupporting
confidence: 69%
“…On the other hand, SLUG can induce TGF-β3 [10] which together may propose a molecular cascade with TGF-β, WNT and NOTCH interfaces. These signaling pathways are crucial players in the induction and maintenance of TICs and EMT-TFs as autocrine reinforcing signals in metastasis and also stemness [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…[133][134][135][136] Ye et al used the 4T1 syngeneic mouse model to demonstrate that TGF-b participates in creating a lung pre-metastatic microenvironment by modulating certain inflammatory cytokines (S100A8/A9) and growth factors (VEGF, Angpt2). 137 Park et al found that IN-1130, a novel TGFb¡1 receptor kinase (ALK5) inhibitor, could suppress lung metastasis in the 4T1 breast cancer orthotopic xenograft mouse model.…”
Section: Transforming Growth Factor B (Tgf-b)mentioning
confidence: 99%
“…In our laboratory, we have shown that TGFb permits advanced breast cancer cell lines 4T1 and MDA-MB-231 to acquire invasive and metastatic properties (Ye et al 2013). Moreover, TGFb also influences stromal, immune, vascular, and cancer stem cells to control features of the microenvironment (Padua et al 2008;Hembruff et al 2010;Drabsch and ten Dijke 2011;Fazilaty et al 2013). …”
Section: Introductionmentioning
confidence: 99%